Do results-based management frameworks frustrate or facilitate effective development practice? Irish international development sector experiences. Issue 6 (18th August 2019) - Murphy, Susan P.; Friel, Enida; McKiernan, Grace; Considine, Patrick; De Marco, Angelina; Cunningham, Aaron; Middlehurst, Molly
ABSTRACT: Utilising a case study methodological approach to analyse the Irish practitioner experience, this article examines if the introduction of results-based frameworks (RBFs) have led to greater impact and accountability to beneficiaries. The findings point to evidence of early resistance to RBFs based upon concerns regarding resources, inflexibility in programming, and the perceived focus on accountability to donors over beneficiaries. However, findings also point to opportunities that could facilitate more effective development in practice. Indications suggest RBFs may facilitate a greater understanding of complexity, increased focus on outcomes and impact through a systematic use of baseline measurements, and improved adaptive programming.